XMCD studies of thin Co films on BaTiO3. (27th July 2015) - Welke, M; Gräfe, J; Govind, R K; Babu, V H; Trautmann, M; Schindler, K-M; Denecke, R
Abstract: Different layer thicknesses of cobalt ranging from 2.6 Å (1.5 ML) up to 55 Å (30.5 ML) deposited on ferroelectric BaTiO3 have been studied regarding their magnetic behavior. The layers have been characterized using XMCD spectroscopy at remanent magnetization. After careful data analysis the magnetic moments of the cobalt could be determined using the sum rule formalism. There is a sudden and abrupt onset in magnetism starting at thicknesses of 9 Å (5 ML) of cobalt for measurements at 120 K and of 10 Å (5.5 ML) if measured at room temperature. Initial island growth and subsequent coalescence of Co on BaTiO3 is suggested to explain the sudden onset. In that context, no magnetically dead layers are observed.